2006
DOI: 10.1111/j.1365-2486.2006.01130.x
|View full text |Cite
|
Sign up to set email alerts
|

A stable isotopic investigation into the causes of decline in a sub‐Antarctic predator, the rockhopper penguin Eudyptes chrysocome

Abstract: The rockhopper penguin (Eudyptes chrysocome) is a conspicuous apex marine predator that has experienced marked population declines throughout most of its circumpolar breeding distribution. The cause(s) for the declines remain elusive, but the relatively large spatio-temporal scale over which population decreases have occurred implies that ecosystem-scale, at-sea factors are likely to be involved. We employ stable isotope analyses of carbon ( 13 C/ 12 C, expressed as d 13 C) and nitrogen ( 15 N/ 14 N, d 15 N) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
134
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(142 citation statements)
references
References 52 publications
(73 reference statements)
6
134
2
Order By: Relevance
“…This contrasts with other seabirds over similar time frames in the North Atlantic [38,51], North Pacific [18,52], and Indian and southern Oceans [53][54][55]. While we found that ivory gull stable-isotope values remained constant, their diet could have changed to different prey with similar isotopic values.…”
Section: Discussioncontrasting
confidence: 52%
“…This contrasts with other seabirds over similar time frames in the North Atlantic [38,51], North Pacific [18,52], and Indian and southern Oceans [53][54][55]. While we found that ivory gull stable-isotope values remained constant, their diet could have changed to different prey with similar isotopic values.…”
Section: Discussioncontrasting
confidence: 52%
“…In turn, the latter resulted in earlier egg-laying dates with increased clutch masses (Dehnhard et al 2015b) and an overall higher breeding success (Crawford et al 2008). However, over the past decades, the global Rockhopper Penguin population has significantly decreased (Pütz et al 2013), with declines related to both decreasing (Guinard et al 1998) or increasing SST (Cunningham and Moors 1994;Thompson and Sagar 2002;Hilton et al 2006;Raya Rey et al 2007), indicating that these birds are highly sensitive to changes in SST in either direction. As a specific example, in 2016, a mass mortality occurred in SRP in the Falklands during the molting period, which was attributed to pre-molt starvation following much colder than usual sea temperatures, which in turn was assumed to have resulted in reduced food availability (Crofts and Stanworth 2017;Morgenthaler et al 2018).…”
Section: Trip Duration and Sstmentioning
confidence: 99%
“…Secondly, fossil carbon introduced into the atmosphere has a lower δ 13 C value than background carbon, thus inducing an accelerating decrease in δ 13 C in the biosphere (the Suess effect; Keeling 1979). Since the Suess effect decreases with increasing latitudes (Hilton et al 2006), the raw δ …”
Section: Data Analysesmentioning
confidence: 99%
“…When long time series of historical and recent samples of δ 13 C are analysed, the raw δ 13 C values have to be adjusted according to the increase in atmospheric CO 2 in response to human fossil fuel burning (Hilton et al 2006). Firstly, the resulting rise in aqueous CO 2 increases, in turn, the phytoplankton fractionation, thus reducing its δ 13 C isotopic values (Rau et al 1992).…”
Section: Data Analysesmentioning
confidence: 99%